Can an artist be mature? Rorschach studies of prominent Polish actors - Mróz, Barbara (Current Problems of Psychiatry, 2024)
Introduction: The peculiarities of being a prominent actor - the unity of the person and the work, recognition and significance - have made possible new and relevant from the point of view of personality and creativity psychology to analyze using the Rorschach method.Objective: The purpose of the study was to assess the personality maturity, type of experiencing, social contacts of prominent Polish actors by means of a qualitative method.Method: The Rorschach Test according to the American signing system of Z. Piotrowski. The study group consisted of 120 Polish actors: 40 outstanding Polish actors, also known in the world from international films or received awards (group A), 40 actors working in theaters in large cities (B), 40 actors employed in theaters in small cities(C). The groups were matched for age (M= 44.7 years, SD 9.31).Results: Analysis of the level of differences in maturity proved statistically significant. The study showed indicators of rivalry, which can stimulate aggressive behavior, for example, but the overall profile indicates good adaptation and control of emotions. The psychogram was dominated by signatures indicating an ambidextrous, differentiated type of experiencing,signifying creative imagination, a tendency to reflect, which is at the same time balanced by external activity,good adaptation.Discussion: The respondents' life activity is characterized by decisiveness, with a tinge of aggression. This attitude can be a cause conflicts with people who may be perceived as rivals, the results of other researchers also indicate.Conclusions: The study of prominent actors using the Rorschach test was conducted for the first time on such a scale, providing many valuable findings.